2021
DOI: 10.3389/fcell.2021.674919
|View full text |Cite
|
Sign up to set email alerts
|

The Role of RNA Methyltransferase METTL3 in Hepatocellular Carcinoma: Results and Perspectives

Abstract: Hepatocellular carcinoma (HCC) is the 6th most prevalent cancer and the 4th leading cause of cancer-related death worldwide. Mechanisms explaining the carcinogenesis of HCC are not clear yet. In recent years, rapid development of N6-methyladenosine (m6A) modification provides a fresh approach to disclosing this mystery. As the most prevalent mRNA modification in eukaryotes, m6A modification is capable to post-transcriptionally affect RNA splicing, stability, and translation, thus participating in a variety of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 98 publications
2
13
0
Order By: Relevance
“…Also, METTL3 was found to be consistently upregulated, and high METTL3 expression was associated with the prognosis of oral squamous cell carcinoma patients. It is also reported that METTL3 overexpression promotes the proliferation and migration of hepatocellular carcinoma cells [45]. Besides, m6A modification in cancer treatment indicates new directions for the treatment of various cancers [15].…”
Section: Discussionmentioning
confidence: 98%
“…Also, METTL3 was found to be consistently upregulated, and high METTL3 expression was associated with the prognosis of oral squamous cell carcinoma patients. It is also reported that METTL3 overexpression promotes the proliferation and migration of hepatocellular carcinoma cells [45]. Besides, m6A modification in cancer treatment indicates new directions for the treatment of various cancers [15].…”
Section: Discussionmentioning
confidence: 98%
“…METTL3 is a pivotal methyltransferase and essential to the performance of m6A modification. 16 METTL3 can regulate RNA expression in a m6A-dependent manner and contributes to the carcinogenesis, tumor progression and drug resistance of HCC. YTHDF2, which is also known as an m6A “reader”,is capable of recognizing and binding to m6A modified sequences.…”
Section: Discussionmentioning
confidence: 99%
“…METTL3 plays a dual role as either an oncogene or a tumor suppressor gene in various types of cancers, including hepatocellular carcinoma (HCC) [ 60 , 61 ], hepatoblastoma [ 62 ], gastric cancer (GC) [ 63 ], colorectal cancer (CRC) [ 64 ], non-small cell lung cancer (NSCLC) [ 65 , 66 ], and bladder cancer (BLC) [ 67 , 68 ]. Abnormal expression of METTL3 in tumor cells affects the infiltration of immune cells.…”
Section: Role Of M 6 a Modification In Remodeling ...mentioning
confidence: 99%